Association of an IGHV3-66 gene variant with Kawasaki disease - Johnson, Todd A.; Mashimo, Yoichi; Wu, Jer-Yuarn; Yoon, Dankyu; Hata, Akira; Kubo, Michiaki; Takahashi, Atsushi; Tsunoda, Tatsuhiko; Ozaki, Kouichi; Tanaka, Toshihiro; Ito, Kaoru; Suzuki, Hiroyuki; et al. (Journal of human genetics, 2021)
In a meta-analysis of three GWAS for susceptibility to Kawasaki disease (KD) conducted in Japan, Korea, and Taiwan and follow-up studies with a total of 11,265 subjects (3428 cases and 7837 controls), a significantly associated SNV in the immunoglobulin heavy variable gene ( IGHV ) cluster in 14q33.32 was identified (rs4774175; OR = 1.20, P = 6.0 × 10 −9 ). Investigation of nonsynonymous SNVs of the IGHV cluster in 9335 Japanese subjects identified the C allele of rs6423677, located in IGHV3-66 , as the most significant reproducible association (OR = 1.25, P = 6.8 × 10 −10 in 3603 cases and 5731 controls). We observed highly skewed allelic usage of IGHV3-66 , wherein the rs6423677 A allele was nearly abolished in the transcripts in peripheral blood mononuclear cells of both KD patients and healthy adults. Association of the high-expression allele with KD strongly indicates some active roles of B-cells or endogenous immunoglobulins in the disease pathogenesis. Considering that significant association of SNVs in the IGHV region with disease susceptibility was previously known only for rheumatic heart disease (RHD), a complication of acute rheumatic fever (ARF), these observations suggest that common B-cell related mechanisms may mediate the symptomology of KD and ARF as well as RHD.